2015
DOI: 10.1016/j.cell.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Hypervulnerability to Sound Exposure through Impaired Adaptive Proliferation of Peroxisomes

Abstract: A deficiency in pejvakin, a protein of unknown function, causes a strikingly heterogeneous form of human deafness. Pejvakin-deficient (Pjvk(-/-)) mice also exhibit variable auditory phenotypes. Correlation between their hearing thresholds and the number of pups per cage suggest a possible harmful effect of pup vocalizations. Direct sound or electrical stimulation show that the cochlear sensory hair cells and auditory pathway neurons of Pjvk(-/-) mice and patients are exceptionally vulnerable to sound. Subcellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 31 publications
8
147
1
1
Order By: Relevance
“…In the interest of space, I will mainly focus on the three animal models in which the greatest extension in lifespan has been reported: C. elegans, D. melanogaster and M. musculus. For the same reason, I will not discuss ROS generated outside the mitochondrion, although it is clear that they can also contribute to the onset of aging and age-related disease [26,27]. For example, it has recently been shown that lifespan of the longlived clk-1 mutant worm is further extended by increasing mitochondrial ROS levels through knock-out of sod2 [28].…”
Section: Introductionmentioning
confidence: 96%
“…In the interest of space, I will mainly focus on the three animal models in which the greatest extension in lifespan has been reported: C. elegans, D. melanogaster and M. musculus. For the same reason, I will not discuss ROS generated outside the mitochondrion, although it is clear that they can also contribute to the onset of aging and age-related disease [26,27]. For example, it has recently been shown that lifespan of the longlived clk-1 mutant worm is further extended by increasing mitochondrial ROS levels through knock-out of sod2 [28].…”
Section: Introductionmentioning
confidence: 96%
“…Electrophysiological whole-cell patchclamp recordings of hair cell mechanoelectrical transduction currents were carried out in cochlear explants from P8.5 mice, as described by Michalski et al (42). ABRs to sound stimuli were recorded and analyzed as previously described (43). The various tests to assess vestibular function were carried out as previously reported (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, some genes have been found to affect the susceptibility to noise in animal models [13, 14]. Several of the knockout mouse lines that have been developed, including Pjvk −/− [15], PMCA2 +/− [16], P2RX2 −/− [17], and CDH23 +/− [18], were determined to be more sensitive to noise than their wild type controls. Meanwhile, more studies are beginning to search for new NIHL susceptibility genes, and hundreds of single nucleotide polymorphism (SNP) loci have been found in genes involved in different pathways of the inner ear.…”
Section: Introductionmentioning
confidence: 99%